Ecological and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) in Surface Water from Middle and Lower Reaches of the Yellow River. (19th October 2016) - Feng, Jinglan; Hu, Pengtuan; Li, Xiaoying; Liu, Shuhui; Sun, Jianhui
Abstract : In surface water from the middle and lower reaches of the Yellow River, total equivalent concentrations of 16 US EPA priority PAHs were calculated based on the measured concentrations. Ecological risk assessment approaches, including hazard quotient and overlapping areas of probability density curves, were performed to evaluate the combined ecological risks of PAHs to the aquatic organisms. The result from hazard quotient indicated that risk quotient of mollusks and zooplankton surpassed 0.1, suggesting potential risks. The potentially affected fractions of PAHs obtained from overlapping areas of probability density curve varied from 11.2% (dry season) to 5.1% (rainy season), which implied that PAHs had been posing pressures on the ecosystem. Health risk based on the incremental lifetime risk for PAHs was conducted to evaluate human cancer risk and noncarcinogenic hazard in the studied area. The results indicated that health risks mainly came from ingestion exposure pathway. The total cancer risks were in the range of 10 −8 to 10 −7, lower than the baseline value of acceptable risk (10 −6 ). Moreover, non-carcinogenic hazard indices of PAHs ranging from 10 −6 to 10 −5 were much lower than the threshold values (1.0). These results indicated that the water from middle and lower reaches of Yellow River might pose no health risk on local residents as a source of drinking water.